If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + 10 = 6w + 10 Reorder the terms: 10 + 2w = 6w + 10 Reorder the terms: 10 + 2w = 10 + 6w Add '-10' to each side of the equation. 10 + -10 + 2w = 10 + -10 + 6w Combine like terms: 10 + -10 = 0 0 + 2w = 10 + -10 + 6w 2w = 10 + -10 + 6w Combine like terms: 10 + -10 = 0 2w = 0 + 6w 2w = 6w Solving 2w = 6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6w' to each side of the equation. 2w + -6w = 6w + -6w Combine like terms: 2w + -6w = -4w -4w = 6w + -6w Combine like terms: 6w + -6w = 0 -4w = 0 Divide each side by '-4'. w = 0 Simplifying w = 0
| X^2+.5x-105=0 | | 2/3-34=32 | | 47+2.6x=166 | | 3x+9=-45-6x | | 47+2.6x=167 | | 7-1/8k=32 | | 47+2.6x=170 | | 8k+1=17whatisk | | -28x+22x= | | 64+2.3x=170 | | -22+28-x= | | x^2/(0.1-x)=3.5*10^-4 | | X(5x-13)=0 | | 11=t/7 | | -23+18+x= | | 64+2.3x=70 | | h/8=8/18 | | 8x-67=41 | | a*b=-2 | | -18x+23x= | | 4ln(x)-5=4 | | 3t-9t=36 | | e^9x+4=9 | | -1.3c=-65 | | -9c-16=c+24 | | 4x+9+7x-2=90 | | 4x^2+20x-11=4 | | 10x+20=25x+15 | | 4x+9+7-2x=90 | | 3xyz/2x-4=0 | | 2/3x-2=6x-14 | | [4x-8]=16 |